Penerapan Model Project Based Learning Berbantuan Media Wattpad Dalam Pembelajaran Menulis Puisi Pada Peserta Didik Kelas VIII SMPN 25 Semarang Tahun Ajaran 2023/2024 - Rosa Aprilia; Ngatmini Ngatmini; Arisul Ulumuddin (Lembaga Pengembangan Kinerja Dosen, 2024)
This study is motivated by the students' poetry writing skills are often hampered due to lack of focus, difficulty expressing feelings due to uncomfortable situations, low interest in writing, less time, and less optimal use of a variety of learning models and media so that the results obtained by students are less than optimal. Therefore, it is necessary to apply other innovative models and media that are more supportive. So that in this study has a formulation of the problem of how the application of the Project Based Learning model assisted by Wattpad media in writing poetry material for class VIII students of SMPN 25 Semarang in the 2023/2024 academic year. The data collection method of this research is descriptive qualitative. With the subject of class VIII C totaling 33 students. The data collection techniques used in this study were test and non-test techniques. The test technique was carried out by giving a test on writing poetry text through the specified learning media, while the non-test technique was carried out by observation, student questionnaires, interviews, and documentation. So that the application of the Project Based Learning Model assisted by Wattpad Media can be applied with the results of good poetry text work products in learning the material of writing poetry texts on Class VIII Students of SMPN 25 Semarang Academic Year 2023/2024.